Safety and on-treatment efficacy of telaprevir: the early access programme for patients with advanced hepatitis C. Issue 7 (7th November 2013) - Colombo, M; Fernández, I; Abdurakhmanov, D; Ferreira, P A; Strasser, S I; Urbanek, P; Moreno, C; Streinu-Cercel, A; Verheyen, A; Iraqi, W; DeMasi, R; Hill, A; et al.
Abstract : Background and aim: Severe adverse events (AEs) compromise the outcome of direct antiviral agent-based treatment in patients with advanced liver fibrosis due to HCV infection. HEP3002 is an ongoing multinational programme to evaluate safety and efficacy of telaprevir (TVR) plus pegylated-interferon-α (PEG-IFNα) and ribavirin (RBV) in patients with advanced liver fibrosis caused by HCV genotype 1 (HCV-1). Methods: 1782 patients with HCV-1 and bridging fibrosis or compensated cirrhosis were prospectively recruited from 16 countries worldwide, and treated with 12 weeks of TVR plus PEG-IFN/RBV, followed by 12 or 36 weeks of PEG-IFN and RBV (PR) alone dependent on virological response to treatment and previous response type. Results: 1587 patients completed 12 weeks of triple therapy and 4 weeks of PR tail (53% cirrhosis, 22% HCV-1a). By week 12, HCV RNA was undetectable in 85% of naives, 88% of relapsers, 80% of partial responders and 72% of null responders. Overall, 931 patients (59%) developed grade 1–4 anaemia (grade 3/4 in 31%), 630 (40%) dose reduced RBV, 332 (21%) received erythropoietin and 157 (10%) were transfused. Age and female gender were the strongest predictors of anaemia. 64 patients (4%) developed a grade 3/4 rash. Discontinuation of TVR due to AEs was necessary in 193 patients (12%). Seven patients died (0.4%, six had cirrhosis). Conclusions: In compensated patients with advanced fibrosis due to HCV-1, triple therapy with TVR led to satisfactory rates of safety, tolerability and on-treatment virological response with adequate managements of AEs.